Chapter 17 Samhandling and Trust in Military Leadership Structures - Bergh , Johan (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The purpose of this chapter is to discuss the importance of trust in military samhandling. Trust serves as one of the main prerequisites for effective collaboration (Kouzes & Posner, 2003). The Norwegian Armed Forces' (NAF) core business is the planning and execution of military operations (Forsvarsstaben, 2014). One of the main tasks of the NAF is to plan for the unexpected and, ultimately, for war. The chapter further discuss trust in military leadership, and leadership and situational awareness. Leadership as a social interaction process that builds trust is discussed, and samhandling is seen in a military context. A basic "trust-based model" of samhandling is introduced and viewed in terms of internal and external framework factors. The chapter concludes that trust is still quite an open concept, and that trust is essential for the effective accomplishment of military missions. The basic trust model is an attempt to underline understanding of the importance of trust in a military planning and leadership context."